Vascular rarefaction mediates whitening of brown fat in obesity - Shimizu, Ippei (American Society for Clinical Investigation, 2014)
Brown adipose tissue (BAT) is a highly vascularized organ with abundant mitochondria that produce heat through uncoupled respiration. Obesity is associated with a reduction of BAT function; however, it is unknown how obesity promotes dysfunctional BAT. Here, using a murine model of diet-induced obesity, we determined that obesity causes capillary rarefaction and functional hypoxia in BAT, leading to a BAT “whitening” phenotype that is characterized by mitochondrial dysfunction, lipid droplet accumulation, and decreased expression of Vegfa. Targeted deletion of Vegfa in adipose tissue of nonobese mice resulted in BAT whitening, supporting a role for decreased vascularity in obesity-associated BAT. Conversely, introduction of VEGF-A specifically into BAT of obese mice restored vascularity, ameliorated brown adipocyte dysfunction, and improved insulin sensitivity. The capillary rarefaction in BAT that was brought about by obesity or Vegfa ablation diminished β-adrenergic signaling, increased mitochondrial ROS production, and promoted mitophagy. These data indicate that overnutrition leads to the development of a hypoxic state in BAT, causing it to whiten through mitochondrial dysfunction and loss. Furthermore, these results link obesity-associated BAT whitening to impaired systemic glucose metabolism.